The role of emotion in moral judgment: the rebirth of traditional Chinese ethical thought in modern psychology - Xiaobo Yu (Trans/Form/Ação)
In traditional Chinese philosophy, emotions were often critiqued as disruptive forces that could undermine moral clarity and social harmony. This perspective, prevalent in Confucian and Daoist thought, emphasized the need for self-control and rationality over emotional expression. The role of emotion in moral judgment was traditionally subordinated to reason and social norms. However, modern psychology highlights the significance of emotions in ethical decision-making and moral judgments, suggesting that emotions play a crucial role in empathy, moral intuition, and relational understanding. Reconciling these views involves integrating traditional Chinese values of emotional restraint with contemporary insights on the constructive role of emotions. By recognizing that emotions can inform and enhance moral reasoning, traditional Chinese ethics can adapt and thrive in the modern era, gaining renewed relevance by acknowledging the complex interplay between reason and emotion.